KAITAN BIAYA DAN TEKNIK PEREMAJAAN KELAPA SAWIT RAKYAT - Indah Minsyah, Nur (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2020)
Linkages between Costs and Rejuvenation Techniques of People's Palm Oil. Palm oil commodity occupies an important and quite strategic position for Jamb Province, which is; 1). As a large foreign exchange earner; 2). Involving approximately 206,787 families and workers; 3). Acceleration of regional / regional development; 4). Opening the field of business and employment; 5). Reducing poverty, and; 6). Improving the welfare of farmers and society. Writing this paper aims to provide an overview: 1). The area of ​​oil palm plantation that needs to be rejuvenated; 2). The amount of costs and the choice of spelling techniques. The data used are secondary data and other relevant information. Of the total plantation area of ​​Jambi Province, around 48% (791,025 ha) is an oil palm plantation area, consisting of 59.11% of community plantations, 38.26% of PBS plantations, and 2.63.% Of PTPN 6. farms. By age, up to 2020 the area covered by should be rejuvenated to reach 185,834 ha. For state-owned oil and palm oil plantation companies (PTPN), to rejuvenate plantations with conventional techniques, their oil palms relatively face no constraints, because they have the funds and or access to the required costs more openly. Whereas for farmers, most of them, to rejuvenate their oil palms in accordance with the economic age and carried out conventionally is difficult to do, because of the absence / lack of funds or capital required, in addition to losing the main source of income as long as the oil palm has not produced. Intercroping rejuvenation technique is the most choice that will be done by farmers.